Ultrasound- and fluoroscopic-guided, percutaneous cholecystostomy drain placement in canine cadavers, a feasibility and safety study - Ordobazari, Jasmin; Pfeiffer, Charlotte; Wang-Leandro, Adriano; Volk, Holger A.; Karbe, Georga T. (Frontiers in Veterinary Science, 2025)
ObjectiveTo evaluate the feasibility and safety of placing cholecystostomy drains percutaneously under ultrasound and fluoroscopy guidance.Study designExperimental cadaveric study.AnimalsTen canine cadavers.MethodsPlacement of two different locking loop drain systems was tested, an 8F pediatric-nephrostomy (Boston Scientific PNPAS) and a 6.5F SUB-nephrostomy (Norfolk Vet Products). The drains were placed into the gallbladders using a Seldinger-technique under ultrasound and fluoroscopic guidance. After placement, CT-scans were performed to assess drain position, leakage and organ injuries. Anatomic examination was performed to identify and grade iatrogenic injury to the abdominal and thoracic organs. Leak pressures were measured using a water manometer. Procedure time, volume injected and pressure measurements before and at the time of leakage were recorded.ResultsDrain placement into the gallbladder was confirmed by ultrasound and fluoroscopy in 5/5 pediatric-nephrostomy and 0/5 SUB-nephrostomy drains. Mean placement time was 10 min (range 7–12 min) for pediatric-nephrostomy drains. CT-scans confirmed drain placement in 4/5 pediatric-nephrostomy drains, one drain had dislodged. Free abdominal contrast was observed in 4/5 dogs with pediatric-nephrostomy. Drains were placed through the 5th to 10th intercostal space. Anatomic examination showed perforation of the pleural cavity (3/10) for drains placed through the 5th, 7th, and 10th intercostal spaces. Drains passed through the liver parenchyma in the same three dogs. The remaining seven dogs had no organ damage. Pressure testing was performed in the pediatric-nephrostomy drains (4/5). Leakage occurred at a pressure of 4, 9, 12 and 18 cm H2O. Leaks were seen at other sites of the gallbladder prior to leaking at the drain entrance point.ConclusionPercutaneous cholecystostomy drain placement is feasible in dogs depending on the drain and technique. Risk of pleural space injury must be considered when performing this method. Further studies are needed to establish a safe, standardized percutaneous cholecystostomy technique.Clinical significanceImaging-guided, percutaneous cholecystostomy drain placement with the tested method is feasible depending on the drain type. Safety concerns must be addressed prior to clinical application.